1983
DOI: 10.1164/arrd.1983.127.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine Aerosol Attenuates Airway Constriction in Dogs with Hyperreactive Airways1–4

Abstract: We investigated the ability of a calcium channel blocker nifedipine, given as an aerosol, to attenuate bronchoconstriction induced by citric acid, Ascaris antigen, and methacholine in Basenji-Greyhound dogs. citric acid 10% increased pulmonary resistance (RL) 4.2-fold +/- 1.0 (mean +/- SEM) and 1.7-fold +/- 0.7 in untreated and nifedipine-pretreated dogs (P less than 0.05). Dynamic compliance (Cdyn) fell to 0.58 +/- 0.07 and 0.66 +/- 0.07 of control values in untreated and nifedipine-treated dogs, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The contraction of bronchial smooth muscle and the release of chemical mediators from mast cells are both dependent on the influx of calcium ions across cell membranes from the ex tracellular to intracellular compartment. Several studies showed the effect of cal cium antagonists (verapamil and nifedi pine) on exercise-induced asthma [1,3,21] and even on antigen-induced bronchocon striction [2,12,22,23]. Some investigators demonstrated the antagonist action of verapamil and nifedipine on the anaphyl actic contraction of smooth muscle [14] and on the release of platelet-activating factor and slow-reacting substances of an aphylaxis from human neutrophils and from human lung [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The contraction of bronchial smooth muscle and the release of chemical mediators from mast cells are both dependent on the influx of calcium ions across cell membranes from the ex tracellular to intracellular compartment. Several studies showed the effect of cal cium antagonists (verapamil and nifedi pine) on exercise-induced asthma [1,3,21] and even on antigen-induced bronchocon striction [2,12,22,23]. Some investigators demonstrated the antagonist action of verapamil and nifedipine on the anaphyl actic contraction of smooth muscle [14] and on the release of platelet-activating factor and slow-reacting substances of an aphylaxis from human neutrophils and from human lung [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, calcium antagonists attenuate bronchoconstriction induced by cholinergic agents in dogs [10], guinea pigs [11], patients with coronary ar tery disease [12], and normal human sub jects [13]. Histamine-induced bronchocon striction is also said to be inhibited by cal cium antagonists in guinea pigs [11], dogs [14], and normal human subjects [13].…”
Section: Discussionmentioning
confidence: 99%
“…The ef fects of nifedipine on various nonimmunological stimuli other than exercise are, however, still controversial. Fanta et al [20] in the guinea pig and Brugman et al [21] in the dog were both able to show that nifedipine inhibited or at least attenuated histamine-and/or metacholine-induced bronchoconstriction. Williams et al [10] confirmed these animal findings in hu mans by showing that the concentration of histamine causing a 20% fall in FEV| in asthmatics was increased 3-fold by preme dication with nifedipine 20 mg.…”
Section: Discussionmentioning
confidence: 99%